Wear prediction in dry revolute clearance joints in multibody systems - Flores, Paulo (2014)
The main goal of this work is to develop a methodology for studying and quantifying the wear phenomenon in revolute clearance joints. In the process, a simple model for a revolute joint in the framework of multibody systems formulation is presented. The evaluation of the contact forces developed is based on a continuous contact force model that accounts for the geometrical and materials properties of the colliding bodies. The friction effects due to the contact in the joints are also represented. Then, these contact-impact forces are used to compute the pressure field at the contact zone, which ultimately is employed to quantify the wear developed and caused by the relative sliding motion. In this work, the Archard’s wear model is used. A simple planar multibody mechanical system is used to perform numerical simulations, in order to discuss the assumptions and procedures adopted throughout this work. From the main results obtained, it can be drawn that the wear phenomenon is not uniformly distributed around the joint surface, owing to the fact that the contact between the joint elements is wider and more frequent is some specific regions.